Perilaku Masyarakat Dalam Menghadapi Dampak Kesehatan Akibat Bencana Banjir Di Desa Lubuk Siam, Kabupaten Kampar, Riau - Gebrina Reski; Zahtamal Zahtamal (Fakultas Kedokteran Universitas Riau, 2021)
Riau Province is one of the areas in Indonesia that is prone to flooding, one of which is in the village of Lubuk Siam, Siak Hulu District, Kampar Regency. Flood conditions that have a negative impact are often caused by the low behavior of the community. The purpose of this study was to determine the behavior of the community in dealing with the health impacts of the flood disaster. This type of research is descriptive qualitative with a phenomenological approach. This research was conducted in Lubuk Siam Village, Siak Hulu District, Kampar Regency, Riau Province. The informants in this study were 16 participant consisting of the community, the village head and staff, representatives of the puskesmas, community leaders and youth leaders who were obtained by purposive sampling technique. The data in this study were analyzed by content analysis. Data collection uses focus group discussions, in-depth interviews, and observations. The results of this study obtained that community behavior in dealing with health impacts due to flooding is still not ideal, some efforts to prevent health impacts and flood disaster management have been good and some have not. In terms of preparedness to face floods, the community has not as a whole prepared evacuation facilities during floods, logistics and medicines as first aid during floods. Treatment efforts if there are family members who experience health effects are still not optimal. Treatment efforts seem to be meager.